Piezoelectric Actuators - Cheng, Tinghai; Li, Jianping (IntechOpen, 2022)
With the rapid development of modern science and technology, great progress has been made in many high-tech fields such as aerospace engineering, ultra-precision machining and assembly, biomedical engineering, precision optical engineering, and micro-electromechanical systems. Since the developmental trajectory of modern high-tech fields is towards high precision and miniaturization, precision driving technology with micro-nano-level positioning accuracy is a key supporting technology. Piezoelectric driving technology has gradually become the main implementation method of micro-nano driving technology due to its high precision, fast response, strong anti-electromagnetic interference, and adaptability under extreme conditions. This book summarizes the latest progress in precision piezoelectric actuators.